Analisis Sentimen Review Aplikasi Mobile Dengan Menggunakan Metode Modified K Nearest Neighbour (MK-NN) - Ahmad Nur Royyan; Indriati Indriati; Lailil Muflikhah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Mobile Applications is a program that runs on mobile devices like Handphone. Especially Smartphone that can accommodate many a program which certainly serves to facilitate users in undergoing their activities. Mobile Banking is required by its users to make transactions that can be done at the ATM. With this application, users do not need to come to the ATM to make transfers or check balances at ATMs. Because it can be done through the Smartphone he has. This is an opportunity for application developers to create Mobile Banking applications that user needs. In the development of this application, They are need the input from users for applications developed in accordance with the needs of its users. Therefore, it takes a method that is able to sort out the sentiments (comments) from the user. Whether the sentiment is included in positive or negative sentiments. In this study, the author used Modified K Nearest Neighbors (MKNN) as the method used to sort the sentiments. The highest accuracy value obtained is 76% for the value of K = 11 with 400 dataset. For 200 training dataset, the highest accuracy is 69% (K=3). And 70% for 300 training dataset and K=3.